Behaviour of reactive sands in concrete - Berezosky, Juan J. (2015)
The concrete of a ring road in the city of Bahía Blanca (Province of Buenos Aires, Argentina) has deteriorated despite ongoing repairs. The extracted cores exhibit cracks parallel to the axis with less significant lateral cracking, which would cause a destructive process in a very short time. Studies were conducted by stereomicroscopy, polarised light microscopy, X-ray diffraction and scanning electron microscopy. The coarse aggregate used is crushed granitic rock and the fine aggregate is natural sand, both of them being frequently used in the Bahía Blanca area. Sand is mainly composed of volcanic rocks with a vitreous matrix and subordinate amounts of sandstones, granitic rocks, quartz, feldspar, mafic minerals and unweathered glass particles. The concrete shows abundant microcracking affecting the matrix and fine aggregates and, in some zones, the coarse aggregates as well. The cracks are usually filled with a birefringent material and are associated with carbonated zones in the matrix. Entrained air voids are partially filled with ettringite. Pavement deterioration has been associated with the development of the alkali-silica reaction due to the presence of potentially reactive materials in the fine aggregate.